Assessment of the antibacterial effect of eighth-generation dentin bonding agent supplemented with propolis on Streptococcus mutans: An in vitro study - Deepa Singh; Moksha Nayak; Vishnuja V R Nair (Scientific Dental Journal, 2023)
Background: The major challenge associated with composite resin is microleakage, which leads to gaps and secondary caries. The prevalent organism responsible for secondary caries is Streptococcus mutans. Objective: The purpose of this study was to evaluate the antibacterial efficacy of an eighth-generation bonding agent (BA) supplemented with propolis against S. mutans. Materials and Methods: A microtiter plate consisting of 96 wells was utilized to assess the antibacterial activity of two experimental groups: Group I (n=16 wells), eighth-generation BA (G-premio bond), and Group II (n=16 wells), eighth-generation BA (G-premio bond) modified with propolis. Each group had four subgroups: “A” well (n= 4), with BA and bacterial suspension in brain heart infusion (BHI); “B” well (n=4), without BA, but with the bacterial suspension in BHI; “C” well (n=4), with BA and BHI, but without bacteria, as negative control; and “D” well (n = 4), only bacterial suspension as positive control. A clinical isolate of S. mutans was procured from the patient’s saliva and dental caries. A direct contact test was used to estimate the bacterial growth by monitoring the changes in optical density values of each well using a spectrophotometer at 600 nm at regular intervals of 30 min, 1, 2, 8, and 16 h. The mean and standard deviation were calculated for each variable. Analysis of the data between the groups was carried out by Tukey’s post hoc test, and a P < 0.05 was considered statistically significant. Results: The study demonstrated statistically significant antibacterial activity in both groups, but the growth of S. mutans was higher in Group I, which used an eighth-generation dentin BA, compared to Group II, which was modified with the addition of propolis. Conclusion: The incorporation of propolis in the eighth-generation dentin BA exerted higher antibacterial activity against S. mutans compared to the unmodified dentin BA.